2008
DOI: 10.1159/000128561
|View full text |Cite
|
Sign up to set email alerts
|

The Anticariogenic Effect of Sugar-Free Gum Containing CPP-ACP Nanocomplexes on Approximal Caries Determined Using Digital Bitewing Radiography

Abstract: This study investigated, using digital bitewing radiography, the progression and regression of approximal caries in adolescent subjects chewing a sugar-free gum containing 54 mg CPP-ACP relative to the identical gum without CPP-ACP. 2,720 subjects from 29 schools were randomly assigned to one of the two gums and were instructed to chew their assigned gum for 3 × 10 min/day, with one session supervised on school days, over the 24-month study period. Standardized digital bitewing radiographs were taken at the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
148
0
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(162 citation statements)
references
References 110 publications
4
148
0
10
Order By: Relevance
“…Caries progression or regression was analyzed, and for subjects chewing the CPP-ACP gum the odds of a surface experiencing caries progression were 18% less. 47 …”
Section: Calcium Based Remineralizing Therapeutic Approachesmentioning
confidence: 99%
“…Caries progression or regression was analyzed, and for subjects chewing the CPP-ACP gum the odds of a surface experiencing caries progression were 18% less. 47 …”
Section: Calcium Based Remineralizing Therapeutic Approachesmentioning
confidence: 99%
“…Pastes containing a complex of casein phosphopeptide (CPP) and amorphous calcium phosphate (ACP), with or without fluoride, have shown potential to prevent dental demineralization, increase remineralization in vitro (10)(11)(12)(13)(14) and to repair initial enamel caries lesions in vivo as well (15)(16)(17). It has been suggested that casein phosphopeptides (CPP) have the ability to stabilize calcium phosphate in solution by binding amorphous calcium phosphate (ACP) with their multiple phosphoserine residues, thereby allowing the formation of small CPP-ACP clusters (18).…”
Section: Introductionmentioning
confidence: 99%
“…One of them was the study that was included in the systematic review of Azarpazhooh et al 7 , which was that of Anderson et al, 9 . The other study refers to that of Morgan et al 19 , in which 2,720 children used chewing gum with or without the addition of CPP-ACP. The follow-up period of the study was 24 months, and regression of caries lesions was observed by means of bite-wing radiographs that allowed visualization of the interproximal dental regions.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…As follows below, there is information about these two new in situ studies and the new in vivo study found by Yengopal & Mickenautsch 8 (Table 4). Yengopal & Mickenautsch 8 observed that in spite of the meta-analysis having been conducted only for in situ studies that presented a short period of exposure to this complex, the promising results of the in vivo studies, one of them with a large sample size 19 and both 9,19 with a longer time of exposure to the CPP-ACP complex (12 to 24 months), suggested the remineralizing effect of the CPP-ACP complex, in studies with long follow-up periods. It is suggested that further randomized in vivo studies, with adequate methodology and longer followup periods should be conducted.…”
Section: Systematic Reviewsmentioning
confidence: 99%